2007
DOI: 10.1128/aac.00972-06
|View full text |Cite
|
Sign up to set email alerts
|

First Characterization of Fluoroquinolone Resistance in Streptococcus suis

Abstract: We have identified and sequenced the genes encoding the quinolone-resistance determining region (QRDR) of ParC and GyrA in fluoroquinolone-susceptible and -resistant Streptococcus suis clinical isolates. Resistance is the consequence of single point mutations in the QRDRs of ParC and GyrA and is not due to clonal spread of resistant strains or horizontal gene transfer with other bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
35
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 34 publications
2
35
0
1
Order By: Relevance
“…Only one strain had a single mutation in GyrB without mutations in GyrA, ParC, or ParE. The resistance mutations in GyrA and ParC in our strains occurred at the expected hot spots (GyrA-S81Y; ParC-S79Y), which are generally similar to those reported by Escudero et al (13) and those in other Gram-positive bacteria, such as S. aureus, S. pneumoniae, S. pyogenes, and E. faecium (18,(24)(25)(26)(27). It has already been demonstrated that QRDR alterations in GyrB and ParE are associated with fl uoroquinolone resistance in Gram-positive bacteria such as S. aureus, S. pneumoniae, and E. faecium (25,27,28), but this has not been reported in S. suis.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Only one strain had a single mutation in GyrB without mutations in GyrA, ParC, or ParE. The resistance mutations in GyrA and ParC in our strains occurred at the expected hot spots (GyrA-S81Y; ParC-S79Y), which are generally similar to those reported by Escudero et al (13) and those in other Gram-positive bacteria, such as S. aureus, S. pneumoniae, S. pyogenes, and E. faecium (18,(24)(25)(26)(27). It has already been demonstrated that QRDR alterations in GyrB and ParE are associated with fl uoroquinolone resistance in Gram-positive bacteria such as S. aureus, S. pneumoniae, and E. faecium (25,27,28), but this has not been reported in S. suis.…”
Section: Discussionsupporting
confidence: 78%
“…Fluorquinolone resistance in S. suis occurs by two mechanisms including mutations in the QRDRs of the gyrA and parC genes and the mediation of FQ effl ux by the SatAB pump (13,15). Based on existing knowledge of FQ resistance and the related literature, the main purpose of our study was to explore the underlying molecular mechanism of FQ resistance after in vitro induction of fl uoroquinolones in S. suis, due to the highly pathogenic nature and zoonotic importance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is known that animals can play important roles as reservoirs and sources of antimicrobial-resistant pathogens (20,21), posing an important concern for public health. Not only the zoonotic circulation of resistant bacteria (6,20,21) but also the spread of antimicrobial resistance determinants between animal and human pathogens has been widely described (1,16). Here we characterized four high-level cefaclor-resistant H. influenzae human clinical isolates recovered between 2000 and 2009 in Spain.…”
mentioning
confidence: 99%